Diversity and abundance of mosquitoes (Diptera, Culicidae) in a fragment of Amazon Cerrado in Macapá, State of Amapá, Brazil - Saraiva, Jose Ferreira; Maitra, Ahana; Souto, Raimundo Nonato Picanço (EntomoBrasilis, 2020)
The Neotropical region has the highest diversity of species, but despite this diversity, this region presents many sampling gaps. The objective of this study was to study the diversity of the mosquitoes of family Culicidae (Diptera: Culicomorpha) as well as to identify the mosquito vectors, in a fragment of Amazon Cerrado in Macapá, Amapá. Three collection methods (Shannon trap, CDC and active collection) were used, and the samples were collected between January to December 2006. 21 species were identified; 11 of them being vectors of malaria, dengue fever, yellow fever, Zika, chikungunya and filariasis; and three of them, Toxorhynchites h. haemorrhoidalis (Fabricius), Wyeomyia melanocephala Dyar & Knab and Wyeomyia aporonoma Dyar & Knab were recorded for the first time from Amapá. The present study contributes to the diversity of mosquitoes (Culicidae) that can be used in additional mapping studies to mitigate epidemic outbreaks in the state of Amapá.